2020
DOI: 10.3390/mi11090832
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Impedance Spectroscopy for Monitoring Chemoresistance of Cancer Cells

Abstract: Electrical impedance spectroscopy (EIS) is an electrokinetic method that allows for the characterization of intrinsic dielectric properties of cells. EIS has emerged in the last decade as a promising method for the characterization of cancerous cells, providing information on inductance, capacitance, and impedance of cells. The individual cell behavior can be quantified using its characteristic phase angle, amplitude, and frequency measurements obtained by fitting the input frequency-dependent cellular respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 106 publications
(172 reference statements)
0
22
0
Order By: Relevance
“…Consequently, the phenotypic heterogeneity within tumors constitutes a major impediment in their diagnostics and therapy. From this point of view, EIS has the ability to monitor the dynamics of intrinsic and extrinsic changes that occur in cancer cells [17].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the phenotypic heterogeneity within tumors constitutes a major impediment in their diagnostics and therapy. From this point of view, EIS has the ability to monitor the dynamics of intrinsic and extrinsic changes that occur in cancer cells [17].…”
Section: Introductionmentioning
confidence: 99%
“…Information regarding the viability and growth of cell is obtained using impedance sensor arrays which are related to attachment, number, and morphology of cells on the surface of electrodes [Hu et al, 2016; Xu et al, 2016]. In addition to cellular behavior and dynamics, cellular impedance analysis can also provide information regarding the biomarkers, sensitivity, and chemo resistivity to therapeutics [Crowell et al, 2020]. Yang et al [2011] noted impedance‐based cellular characteristics at the frequencies of 10, 25, and 50 kHz for oral cancer cells and normal epithelial cells to monitor adhesion, spreading, and proliferation.…”
Section: Cell‐based Electrical Impedance Spectroscopymentioning
confidence: 99%
“…Cell migration, which serves as the initiation of cancer metastasis, could be recorded by ECIS technology [ 157 ]. Primiceri et al demonstrated that cell migration could be monitored and automatically analyzed by a EIS biochip [ 152 ].…”
Section: Applications Of Single-cell Impedance Sensing Technologymentioning
confidence: 99%